On the relationship between mathematics and visuospatial processing in Turner syndrome. (February 2020) - Baker, Joseph M.; Klabunde, Megan; Jo, Booil; Green, Tamar; Reiss, Allan L.
Abstract: A common neurocognitive phenotype of Turner syndrome (TS) includes coincident deficits in math and visuospatial reasoning while overall IQ remains intact. However, research has highlighted disparities in the relationship between these properties in women with TS, suggesting that not all visuospatial domains are equally related to mathematics in this group. Here, we present findings from a longitudinal investigation of visuospatial processing and its relationship to math performance in adolescent girls with TS and age-matched healthy controls. Participants completed a standardized battery of math and visuospatial tests once a year for 4 years. Linear mixed effects modeling was used to examine the relationship between mathematics and each visuospatial domain over time. Our results indicate that math performance was related to visual tracking, visual-motor coordination, and figure-ground processing. Such visuospatial domains appear to be uniquely affected by TS and could contribute to their deficits in math performance. Furthermore, differences in math and visuospatial test performance between girls with TS and healthy controls remain stable over time. Our results have important implications for the role of visuospatial processing in early math performance and may inform the development of effective interventions aimed at improving math education in children with TS.